Electronically tunable low-voltage mixed-mode universal biquad filter - Maheshwari S.; Singh S.V.; Chauhan D.S. (My University, 2025)
This study presents an electronically tunable low-voltage mixed-mode universal biquad filter. The proposed filter employs only three current controlled current conveyor trans-conductance amplifiers (CCCCTAs) and two grounded capacitors. The proposed filter can realise low pass, band pass and high pass responses in all the four possible modes, that is, voltage-mode, current-mode, trans-admittance-mode and trans-impedance-mode from the same configuration. The filter can also realise regular notch, low-pass notch, high-pass notch and all pass responses in current and trans-admittance-mode, with interconnection of relevant output currents. The filter parameters namely pole frequency, quality factor, bandwidth and filter gains can be tuned electronically. Moreover, the circuit parameters such as pole frequency and quality factor can be simultaneously current controlled without affecting bandwidth. Effects of non-idealities and parasitic are also discussed. The circuit possesses low active and passive sensitivity and can be operated at low power supply (±1 V). The validity of the proposed filter is verified through computer simulations using PSPICE, the industry standard tool. Possible experimental setup for CCCCTA using commercial available integrated circuits is further discussed. © 2011 The Institution of Engineering and Technology.